Autoaggressive dermatoses in the practice of a dermatovenereologist - Vera V. Ryabova; Anna L. Evseeva; Sergei V. Koshkin (State Scientific Center of Dermatovenereology and Cosmetology, 2022)
The article presents clinical cases of autoaggressive dermatoses from the own practice of authors. In the first case, the patient turned to a cosmetologist for the purpose of aesthetic correction of scars; it was found that she inflicted self-harm unconsciously against the background of long-term depression and psycho-emotional stress associated with instilling a sense of guilt for the absence of children in the family. Against the background of the recurrent nature of the skin process, the patient is strongly recommended consultation and treatment by a psychotherapist. The following two cases share common features: the presence of parasites under the skin, with which patients independently fought with radical methods. The first patient was identified retrospectively upon admission to the venereology department, and according to the patient, he already cured the tick on his own. In the second case, the demonstrative type of behavior and flaunting his own state attracts attention. This patient with a diagnosis of neurotic excoriations (dermatozoic delusions?), examination by a neurologist and a psychotherapist is recommended.